Primary Total Knee Arthroplasty Twenty Years after Distal Femoral Cement Augmentation of a Giant Cell Tumor - Alejandro Zylberberg; Gillian Bayley; Luca Gala; Paul R. Kim (Case Reports in Orthopedics)
We present a case of knee reconstruction 20 years after treatment of a giant cell tumor (GCT) with curettage and cementation. There is currently an ongoing debate whether cement or allograft bone is the preferred material for filling the void after GCT curettage. In this case we were able to readily implant a primary total knee replacement without disturbing the existing well-interdigitated large cement bolus and did not require any stems or augments for the reconstruction. Given the ease of TKR implantation in this patient, we feel that the use of cement following curettage of a GCT lesion is a better choice than allograft bone which may not provide enough structural support for the knee reconstruction and lead to a much more extensive procedure.